2016
DOI: 10.1016/j.ijsu.2016.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery for the treatment of pilonidal disease. The Gips procedure on 2347 patients

Abstract: the Gips procedure for the treatment of pilonidal disease is safe and feasible. It has a low complication and recurrence rate, early return to daily activities and offers a good cosmetic result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 22 publications
4
41
0
Order By: Relevance
“…Following the excision towards the sacral fascia, open healing (OH) and primary closure (PC) are still the most commonly used surgical techniques. PC can be done in the form of asymmetric (OMPCT) or midline closure (4,20). In their meta-analysis, McCallum et al reported that the PC provided rapid recovery despite the high risk of recurrence compared to OH, and emphasized the importance of using OMPCT as a standard treatment if PC is preferred in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…Following the excision towards the sacral fascia, open healing (OH) and primary closure (PC) are still the most commonly used surgical techniques. PC can be done in the form of asymmetric (OMPCT) or midline closure (4,20). In their meta-analysis, McCallum et al reported that the PC provided rapid recovery despite the high risk of recurrence compared to OH, and emphasized the importance of using OMPCT as a standard treatment if PC is preferred in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…Gips popularized this method by using trephines instead of a scalpel for the excision. Results of the Lord and Millar/ Gips technique in over 7000 patients have been described in 9 reports [4,7,11,18,19,22,28,30]. The reported recurrence rates vary from 3 to 28%, with around 25% in the larger studies with longer follow-up.…”
Section: Excision Of Sinuses Through Minimal Separate Excisionsmentioning
confidence: 99%
“…The median time to wound healing is about 25 days in most studies. However, delayed healing may occur in about 10 to 16% [4,6,11]. Khodakaram [17] described a modification of the Lord-Millar method where the wounds from the small midline excisions were closed primarily (.…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…Minimally invasive surgical procedures usually performed through a limited incision or excision of the sinuses and orifices. The resulting wound can be left open, curetted or partially treated (9)(10)(11)(12)(13) . Similar to these procedures, we performed a minimal incision in the sinuses and orifices and included only the diseased tissue in the excision.…”
Section: Introductionmentioning
confidence: 99%